Design of a Suspended Stripline Narrow Bandpass Filter with Ultrawideband Harmonic Suppression - Ju Seong Park; Wahab Mohyuddin; Hyun Chul Choi; Kang Wook Kim (International Journal of Antennas and Propagation)
A design method of narrow bandpass filters (NBPFs) of 4–6% bandwidth with ultrawideband suppression of harmonic passbands, utilizing two cascaded step impedance resonators (SIRs) in a suspended stripline, is proposed in this paper. The proposed design utilized the characteristics of a suspended stripline, which provides a much higher characteristic impedance ratio as compared with that of the microstripline, enabling ultrawideband harmonic suppression. As an example of the NBPF, a filter with a passband center frequency f0 of 0.75 GHz and bandwidth of 5% was implemented and proved to suppress the harmonic passbands up to 13.5 f0. Since the proposed filter was implemented on the suspended stripline, the passband insertion loss was only −0.9 dB, which is low as compared with other previous designs. The proposed filter is a compact high-performance low-loss NBPF, which can be applicable to various wireless systems.